FAKTOR-FAKTOR YANG MEMENGARUHI PERBANKAN DALAM MEMPREDIKSI BANKING DISTRESS DENGAN METODE CD INDEKS - IKA FEBRIANA, SINTYA (Jurnal Ilmu Manajemen (JIM), 2019)
AbstractThe bank is a financial intermediary that collects funds from the community and redistributes it to the community and provides other banking services. As an intermediary institution, banks cannot be separated from risks that are influenced by internal factors and external factors that can cause banking distress conditions. This study aims to examine the effect of internal banking factors and macroeconomic variables on predictions of banking distress in banks in Indonesia by using the crisis and default index (CDI). The internal variables used in this study are Risk profiles that are proxied by NPL and LDR; Good corporate governance that is proxied by the size of the board of directors; Earning is proxied by ROA, ROE, BOPO, NIM; and Capital which is proxied by CAR. While the macroeconomic variables used are economic growth, inflation, and exchange rates. This study used 27 conventional banks in Indonesia as samples during the period 2013-2017. The analysis technique used is logistic regression. The results of this study indicate that on the internal banking factors the earnings variable that is proxied by ROE has a negative effect on the predictions of banking distress. Keywords: banking distress, crisis and default index, factors internal, Indonesia, macroeconomic